Tea and other diet-related practices in relation to sleep health in midlife women from Mexico City: qualitative and quantitative findings - Zamora, Astrid N.; Roberts, Elizabeth F. S.; Sharp, Lilian; Borra, Catherine; Lee, Jennifer; Téllez-Rojo, Martha M.; Peterson, Karen E.; Torres-Olascoaga, Libni A.; Cantoral, Alejandra; Jansen, Erica C. (Frontiers in Sleep, 2024)
Based on ethnographic interviews among midlife, working-class women from Mexico City, our primary aim was to identify themes related to diet and sleep. Informed by qualitative analyses, a secondary aim was to examine associations between tea and sleep duration in a broader cohort.We conducted a cross-sectional study of ethnographic interviews about sleep and other behaviors, including diet, with a purposive sample of 30 women from the ELEMENT cohort. Ethnographer notes and transcripts were analyzed using thematic analysis. Guided by findings from interviews demonstrating that tea consumption might be associated with sleep, we conducted post hoc analyses of the relationship between tea and sleep duration using data from food frequency questionnaires and actigraphy in the broader cohort (n=406). Results: The mean (SD) age of the ethnographic sample was 50.0 (9.0) years. The top noted theme was the use of herbal tea to improve sleep; most women (29/30) discussed herbal teas, characterizing them as a "natural remedy" to facilitate sleep. The mean (SD) age of the broader sample (N=406) was 48.4 (6.2) years. Post hoc analyses revealed positive associations between tea without sugar and sleep duration. We found that every serving of tea without sugar consumed was associated with an 18.0 min per night [(SE) = 7.8; p = 0.022] and a 13.4 min per night [(SE) =5.6; p = 0.017] increase in weekend and 7-day sleep duration, respectively.Conclusions: Within a sample of 30 midlife women, dietary practices were described related to sleep, specifically the consumption of herbal teas to promote sleep.